Paleobathymetric Study using Foraminifera Microfossil Analysis in the Wonocolo Formation, Tinawun Village Area, Malo District, Bojonegoro Regency, East Java - Bahar, Hendra; Firdaus, Ar Royyan (LPPM Institut Teknologi Adhi Tama Surabaya (ITATS), 2023)
Paleobathymetric study on the Wonocolo Formation in the Tinawun Village Area, Malo District, Bojonegoro Regency, East Java, using microfossil foraminifera analysis from rock samples in that area, aims to obtain information about the depositional environment of sedimentary rocks in the past. The Wonocolo Formation is a rock formation deposited during the Middle to Late Miocene, approximately 11 to 15 million years ago. The analysis of microfossil foraminifera involves the identification and counting of different foraminifera species from rock samples. The method used to determine paleobathymetry is the P/B ratio analysis with the maximum flooding surface (MFS) determined by the maximum abundance of planktonic foraminifera. For the P/B ratio analysis, the classification of planktonic and benthic foraminifera is determined based on their shell morphology. Based on the P/B ratio classification, the paleobathymetry of the Wonocolo Formation can be identified in two main bathymetric zones, namely the Neritic Bathymetric Zone (shallow marine environment) and the Oceanic Bathymetric Zone (deep-sea environment). The research indicates that paleobathymetry in the study area occurred during the Late Miocene (N16, N17, and N18) in an Outer Neritic environment with sea depths ranging from 100 to 200 meters.